Development and validation of a faecal immunochemical test-based model in the work-up of patients with iron deficiency anaemia - Hernández, Goretti; Quintero, Enrique; Morales-Arraez, Dalia; Rayado, Guillermo García; Hijos-Mallada, Gonzalo; Fernández-Fernández, Nereida; Castro-Parga, Luisa de; Álvarez-Sánchez, María Victoria; Olano, Carolina; Rodríguez-Alcalde, Daniel; Amaral-González, Carla; Alonso-Abreu, Inmaculada; et al. (Frontiers in Medicine, 2024)
Objective: In patients with iron deficiency anaemia (IDA), the diagnostic yield of gastroscopy and colonoscopy (bidirectional endoscopy) in detecting neoplastic lesions is low. This study aimed to develop and validate a faecal immunochemical test (FIT)-based model to optimise the work-up of patients with IDA. Methods: Outpatients with IDA were enrolled in a prospective, multicentre study from April 2016 to October 2019. One FIT was performed before bidirectional endoscopy. Significant gastrointestinal lesions were recorded and a combined model developed with variables that were independently associated with significant colorectal lesions in the multivariate analysis. The model cut-off was selected to provide a sensitivity of at least 95% for colorectal cancer (CRC) detection, and its performance was compared to different FIT cut-offs. The data set was randomly split into two groups (developed and validation cohorts). An online calculator was developed for clinical application. Results: The development and validation cohorts included 373 and 160 patients, respectively. The developed model included FIT value, age, and sex. In the development and validation cohorts, a model cut-off of 0.1375 provided a negative predictive value of 98.1% and 96.7% for CRC and 90.7% and 88.3% for significant colorectal lesions, respectively. This combined model reduced the rate of missed significant colorectal lesions compared to FIT alone and could have avoided more than one-fourth of colonoscopies.The FIT-based combined model developed in this study may serve as a useful diagnostic tool to triage IDA patients for early endoscopic referral, resulting in considerable reduction of unnecessary colonoscopies.